The Study of Academic Administration Problems in Small Schools under Nakhon Sawan Primary Educational Service Area Office 1 - สุนทรพรพันธ์ อภิญรัตน์ (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2021)
The purposes of this research were to study and compare the level of academic administration problems in small schools. The sample was 50 school administrators and 176 teachers, 226 samples in total selecting with random sampling. The research instrument was a questionnaire about academic administration problems in small schools with a coefficient of stability at 0.99. The data were analyzed using percentage, mean, standard deviation, t-test analysis, analysis of variance (One-way ANOVA) and paired comparison test by Scheffe’s Method. The Research findings were as follows: 1) All 9 academic administration problems in small schools overall were at a moderate level when sorting by aspect from the highest to the lowest were Internal quality assurance,learning management,Research for educational quality development,curriculum and curriculum development in schools,instructionalmedia and developmentinnovation and educational technology,education guidance,evaluation assessment and course transfer,development learning resource and library,and educational supervision, respectively. 2) The comparison results of the opinions of school administrators and teachers towards the academic administration in small schools divided by sex, education found, and work experience that the participants had different opinions toward the academic administration problems in small schools statistically significant at the .05 level.